The effectiveness of a newly developed smart learning environment for developing Smart Devices Apps Design Skills - Maher, Dalia; Elsayed, Abdelaal; Elnaggar, Mohamed (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The research aimed at examining the impact of a newly developed Smart Learning Environment (SLE) based on two AI-based chatbot modes (text - voice) to develop the design skills of smart mobile apps by using appmachine platform. The developed SLE uses smart tools from the field of Artificial Intelligence for interactive experience, support, and guide for graduate learners to effectively learn smart mobile apps design and development skills. The research sample consisted of 40 randomly selected male and female graduate learners specializing in educational technology at the Faculty of Education, Mansoura University, Egypt. The learners were classified in two equal groups. The content is implemented by two chatbot modes that help the learners to deal with SLE to register, get the learning content, execute the tasks and build the app. The research tools included a list of skills for designing smart mobile applications, and a performance aspects observation card for evaluating the learner design skills. After implementation of the research experiment, the results indicated that there is a positive impact of the two chatbot modes (text - voice) in developing the design skills of smart mobile applications among graduate learners. The environment was designed and developed using the latest available technology standards, approaches, and tools. The environment was tested with a random group of learners as new developers, and showed impressive results with positive impacts. Finally, the main result is the success of all learners to build a complete educational app after the full execution of this research experiment.